Constructivism Thinking and Implementation in Non-Formal Education - Vendri, Rivendri; Jamaris, Jamaris; setiawati, Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
Philosophy is a branch of science that has several realistic, fundamental aspects, values and knowledge that are fundamental in the birth of logical reasoning, critical thinking that discusses the universe, ethics, religion, life, knowledge and truth. In its development there are several schools of philosophy, one of which is the philosophy of constructivism, a thought where contructivism learning is seen as an active process that involves interaction between individuals and their environment. This concept can be applied in non-formal education in various ways. Constructivism thinking in non-formal education emphasizes the importance of active participation and meaningful learning for learners. This approach enables them to develop critical thinking, problem-solving and adaptability skills that are relevant in real life. The implementation of constructivism in non-formal education involves the important role of facilitators or teachers in creating an environment that encourages learners to actively participate and interact in the learning process. Teachers should apply methods that focus on learners, encourage critical thinking, and inspire them to formulate and analyze problems independently.Keywords: Philosophy, Thought, Constructivism, Non-formal education